Disease manifestations of Helicobacter pylori infection in Arctic Canada: using epidemiology to address community concerns. Issue 1 (8th January 2014) - Cheung, Justin; Goodman, Karen J; Girgis, Safwat; Bailey, Robert; Morse, John; Fedorak, Richard N; Geary, Janis; Fagan-Garcia, Katharine; van Zanten, Sander Veldhuyzen; ,
Abstract : Objectives: Helicobacter pylori infection, linked to gastric cancer, is responsible for a large worldwide disease burden. H pylori prevalence and gastric cancer rates are elevated among indigenous Arctic communities, but implementation of prevention strategies is hampered by insufficient information. Some communities in northern Canada have advocated for H pylori prevention research. As a first step, community-driven research was undertaken to describe the H pylori- associated disease burden in concerned communities. Design: Participants in this cross-sectional study completed a clinical interview and gastroscopy with gastric biopsies taken for histopathological examination in February 2008. Setting: Study procedures were carried out at the health centre in Aklavik, Northwest Territories, Canada (population ∼600). Participants: All residents of Aklavik were invited to complete a clinical interview and gastroscopy; 194 (58% female participants; 91% Aboriginal; age range 10–80 years) completed gastroscopy and had gastric biopsies taken. Primary and secondary outcome measures: This analysis estimates the prevalence of gastric abnormalities detected by endoscopy and histopathology, and associations of demographic and clinical variables with H pylori prevalence. Results: Among 194 participants with evaluable gastric biopsies, 66% were H pylori- positive on histology. Among H pylori -positive participants, prevalence was 94% for acute gastritis, 100% for chronic gastritis, 21% for gastric atrophy and 11% for intestinal metaplasia of the gastric mucosa, while chronic inflammation severity was mild in 9%, moderate in 47% and severe in 43%. In a multivariable model, H pylori prevalence was inversely associated with previous gastroscopy, previous H pylori therapy and aspirin use, and was positively associated with alcohol consumption. Conclusions: In this population, H pylori -associated gastric histopathology shows a pattern compatible with elevated risk of gastric cancer. These findings demonstrate that local concern about health risks from H pylori is warranted and provide an example of how epidemiological research can address health priorities identified by communities.